Knowledge and practices associated with compliance with the law that regulates the legal regime of dogs (Law N.° 27596) in the districts of Lima, Peru - Llaja, José (2021)
The aim of this study was to evaluate the knowledge and practices associated with compliance with Law N° 27596, law that regulates the legal regime of dogs, among the population of districts of Lima, Perú. A survey was designed and validated that included variables on knowledge and practices associated with the main regulatory aspects of the law. The survey was applied in public spaces to dog owners from 20 districts of high, medium and low socioeconomic status. Participation in the study was voluntary, obtaining 783 surveys. In general, 67.6% knew about potentially dangerous breeds (they named Pitbull and Rottweiler) and 24.9% knew about the existence of requirements for their possession. Besides, 35.1% said that castration decreased the aggressiveness of the dogs and 24.8% believed that the dogs should be trained in specialized centers, 95% affirmed that the owner of the dog must assume the damages that his dog produces, 29.4% knew that the owners of dogs of potentially dangerous breeds should have insurance against accidents and 58.7% recognized that the National Police should help the dog bite victims. Some acknowledged that their dogs had bitten (12.8%) and 72.0% assumed the expenses caused by their dogs. The practice of collecting faeces and walking the dogs was the majority, but that of identification, registration in the municipality and reproductive control of dogs was limited. Moreover, 14.3% claimed to have received talks on responsible pet ownership, 16.2% heard about Law N° 27596 and 8.4% knew that there was a Municipal Ordinance in relation to that law in their district. It is necessary a greater dissemination of Law N° 27596 as well as a requirement for its application.